Sitting postures and trunk muscle activity in adolescents with and without nonspecific chronic low back pain: an analysis based on subclassification - Astfalck, Roslyn G; O'Sullivan, Peter B; Straker, Leon M; Smith, Anne J; Burnett, Angus; Caneiro, Joao Paulo; Dankaerts, Wim (Spine (Philadelphia, Pa. 1976), 2010)
A preliminary cross-sectional comparative study of adolescents with nonspecific chronic low back pain (NSCLBP) and healthy controls. To investigate whether differences in spinal kinematic and trunk muscle activity exist in both usual and slump sitting in adolescents with NSCLBP. Evidence suggests that low back pain commonly develops in adolescence and increases the risk for low back pain in adulthood. Sitting is an important consideration in adolescents with NSCLBP: currently there are no reports investigating their motor control strategies in sitting. Twenty-eight adolescents (14 female) with NSCLBP and 28 matched pain-free controls were recruited from a large cohort study. Pain subjects were subclassified based on O'Sullivan's classification system. Three-dimensional lumbo-pelvic kinematic data and the activation of 3 back and 2 abdominal muscles were recorded during usual and slump sitting. The flexion-relaxation phenomenon in sitting was also investigated. Spinal posture in usual and slump sitting were similar for adolescents with and without NSCLBP. However, differences were identified in both sitting conditions when those with NSCLPB were subclassified and compared with controls. Muscle activation differences were not consistently identified, with only lower levels of internal oblique activation in usual sitting in NSCLBP compared with pain-free controls showing significance. Flexion relaxation was observed in both iliocostalis and thoracic erector spinae in the NSCLBP group but not controls. This study provides preliminary results. Differences with sitting posture are only seen when adolescents with NSCLBP are classified. Trunk muscle activation is not a sensitive marker for discriminating subgroups of NSCLBP during adolescence.